2015
DOI: 10.1080/00223980.2014.996512
|View full text |Cite
|
Sign up to set email alerts
|

Self-Esteem, Perceived Stress, and Gender During Adolescence: Interactive Links to Different Types of Interpersonal Relationships

Abstract: The goal of this study was to analyze the relationships between self-esteem, perceived stress, the quality of different types of interpersonal relationships, and gender in adolescents. This study used a sample of 1614 adolescent high school students and robust data analytic techniques to test the proposed relationships. The results partially supported the initial hypothesis in that perceived stress mediated the relationships between self-esteem and four of the types of interpersonal relationships (i.e., same-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 50 publications
3
14
0
7
Order By: Relevance
“…We also found that self-esteem was positively associated with resilience and negatively associated with stress. These study findings are consistent with prior research on the relationship of self-esteem with resilience (Arslan, 2015;Karatas & Cakar, 2011), and self-esteem with stress (Bi et al, 2016;Mann et al, 2004).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We also found that self-esteem was positively associated with resilience and negatively associated with stress. These study findings are consistent with prior research on the relationship of self-esteem with resilience (Arslan, 2015;Karatas & Cakar, 2011), and self-esteem with stress (Bi et al, 2016;Mann et al, 2004).…”
Section: Discussionsupporting
confidence: 91%
“…Thus enhanced self-esteem increases levels of resilience (Karatas & Cakar, 2011). Also, Self-esteem has a close relationship with stress, and self-esteem is more likely to reduce stress levels (Bi et al, 2016). Individuals having low levels of self-esteem tend to believe that they are not competent, significant, or worthy and may try to cope with the negative feelings associated with low self-worth, potentially leading to a heightened level of perceived stress (Eisenbarth, 2012).…”
Section: Self-esteem As Mediatormentioning
confidence: 99%
See 1 more Smart Citation
“…Further, we will explore which domains of self-esteem (i.e., scholastic competence, social acceptance, athletic competence, physical appearance, and romantic appeal) contribute with significant unique variance to QoL. In these analyses, we adjust for gender and age because QoL has shown to be gender and age dependent in earlier studies [29], and pronounced gender and age differences have been detected in psychopathology [30,31] and self-esteem [20,32]. Figure 1 depicts the associations to be investigated in our structural equation model.…”
Section: Aims Of the Studymentioning
confidence: 99%
“…Durante la adolescencia, altos niveles de autoestima se asocian con relaciones interpersonales de calidad como factor protector (Bi, Ma, Yuan, y Zhang, 2016) y la baja autoestima a factores de riesgo (Florenzano y Valdés, 2013). A medida que los niños crecen, la autoestima se vuelve más compleja al ser influenciada por más factores como la evaluación de los pares, el rendimiento académico, la apariencia física, las normas sociales, las expectativas de los padres, entre otros, y como consecuencia, la autoestima tendería a disminuir (Cantero et al, 2016;Palacios 2000, citado en De Tejada, 2010.…”
Section: Autoestima Infancia Y Adolescenciaunclassified